Fibers and Forensics : A Review of Textile Analysis in Stab Wound Cases (International Journal of Scientific Research in Science and Technology, 2024)
This paper covers the complex field of forensic textile stabbing analysis, including its past growth, methods, case studies, applications, and database use. The evaluation begins with an outline of its historical background and proceeds to examine diverse analytical techniques and equipment essential for proficient analysis. It follows the development of stab analysis from simple visual inspections to advanced instruments. The review clarifies the critical function of stab analysis in criminal investigations via the lens of case studies and academic publications. The relationship between stab analysis and other forensic specialties is also examined, with a focus on cooperation with material engineering domains. The study emphasizes the value of stab analysis in modern forensic science by demonstrating its potential. This article offers insights to improve analysis procedures and further the cause of justice, making it a useful tool for forensic professionals, advocates, and researchers alike. Through a combination of historical viewpoints, methodological developments, and multidisciplinary efforts, the review facilitates innovation in conventional forensic technology, which in turn helps to resolve complex criminal cases.